Zur Zukunft der Bereichsethiken - Herausforderungen durch die - Maring, Matthias [Hrsg.] (Schriftenreihe des Zentrums für Technik- und Wirtschaftsethik am Karlsruher Institut für Technologie. Hrsg. von Matthias Maring, 2016)
In the present volume "The future of areas of applied ethics - challenges by the economisation of the world" will be dealt with approaches and examples how to face these challenges and what that means for the future of applied ethics. Subjects are among others: the future of engineering, business and science ethics, the economisation of professional and social work, media, personal relationships, water supply, health care and sport.